THE POLITENESS OF ASSERTIVE SPEECH ACTS: SYNERGIZING THE LINGUISTIC POLITENESS DEVICES IN CONFLICT RESOLUTION COMMUNICATION - Ali, Sopyan; Kristina, Diah; Sumarlam, Sumarlam (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2017)
This article studies the realisastion of politeness assertive speech act on the  scholarly dialogue called Religious Freedom Project (RFP) at the Georgetown University, US. The primary data in this article is in the form of written data (document), which is the transcription of the RFP dialogues conversation. In addition to the supplementary data is the video record of the dialogues retrieved from Youtube.  The assertive SA in this study refer to the utterances that bind S to the truth of something he/she expresses. The result shows that there were found the use of six types of assertive speech acts that go hand in hand to reflect the Leech's Politeness Principles, among others the acts of admitting, informing, assuring, arguing, affirming, and reporting. Based on the basis of finding data from 137 speech acts of assertive type, it is concluded that in RFP dialogue, the politeness markers were classified into eight types referring House & Kasper’s, i.e.; hedging, understaters, downtowners, committers (both enhancers and reducers of S’s self commitment), agent-avoiders, intensifiers, overstaters, and politeness markers. Politeness devices or markers reflect a great deal and effect on the production of utterances force in the RFP, all of which were directed toward criticism.Keywords: politeness markers; assertive speech act; politeness maxims; dialogueKESANTUNAN TINDAK TUTUR ASERTIF: MENSINERGIKAN PENANDA-PENANDA SANTUN LINGUISTIK DALAM KOMUNIKASI KONFLIK RESOLUSI AbstrakArtikel ini mengkaji realisasi kesantunan tindak tutur asertif pada dialog lintas agama dan cendikiawan Religious Freedom Project (RFP) di Universitas Georgetown, Amerika Serikat (A.S).Sumber data utama dalam penelitian ini berbentuk data tertulis (dokumen), yaitu teks transkripsi dari video percakapan dan sumber data pendukung yaitu yang berbentuk video rekaman tuturan dialog lintas agama, Religious Freedom Project (RFP) diakses melalui situs portal YouTube. Kesantunan pragmatic dalam kajian ini merangkum pembahasan tentang penerapan maksim/bildal-bidal kesantunan Leech (1983) sebagai konsekuensi penggunaan tindak tutur (TT) asertif beserta indikator perangkat-perangkat santunnya (House & Kasper, 1981). Dalam dialog RFP ditemukan penggunaan enam jenis-jenis TT asertif dominan yang merefleksikan PS-Leech, yakni TT sub-mengakui, menginformasikan, meyakinkan, mengargumentasikan, mengafirmasi, danmelaporkan. Berdasarkan temuan data dapat disimpulkan bahwa dalam dialog RFP perangkat-perangkat santun diklasifikasi menjadi delapan jenis (mengacu taksonomi House & Kasper, 1981), yaitu perangkat berpagar (hedging), pengecil (understaters), penurun (downtowner), perujukdiri (committers, peningkat dan penurun komitmen diri), penghindaran (agent-avoiders), penguat tingkat rasa (intensifiers), dan pengujaran berlebihan (overstaters), perangkat santun (politeness markers). Perangkat santun sebagai elemen linguistic berpengaruh besar terhadap daya tutur dalam komunikasi dialog RFP, kesemuanya secara dominan diarahkan pada tuturan-tuturan mengkritisi.Kata Kunci/frase:  Penanda-penanda kesantunan; tindak tutur asertif; maksim kesantunan; dialog